Electrical characterisation of highly doped triangular silicon nanowires - Za'bah, Nor Farahidah; Kwa, Kelvin S. K.; O’Neill, Anthony (Trans Tech Publications Ltd., Switzerland, 2014)
A top-down silicon nanowire fabrication using a combination of optical lithography and orientation dependent etching (ODE) has been developed using <100> Silicon-on Insulator (SOI) as the starting substrate. Initially, the samples were doped with phosphorus using the diffusion process resulting in carrier concentration of 2 X 10 18 cm-3. After the silicon nanowires were fabricated, they were measured using a dual configuration method which is similar to the four-point probe measurement technique to deduce its resistivity. The data obtained had suggested that the doping distribution in the silicon nanowires were lower and this may have been affected by the surface depletion effect. In addition, with respect to carrier mobility, the effective mobility of electrons extracted using the four-point probe data had demonstrated that the mobility of carriers in the silicon nanowire is comparable with the bulk mobility. This is most probably due to the fact that in this research, the quantum confinement effect on these nanowires is not significant.